The Role of Parental Motivation as a Mediator between Socioeconomic Factors and Temper Tantrum Incidents - Zainal Munir; Nyimas Heny Purwati; Achmad Fauzi (Media Publikasi Cendekia Indonesia, 2026)
Parenting motivation is a critical factor in managing child behavior, as socioeconomic conditions often influence parental emotional responses and children's development. This study aims to analyze the impact of education level, occupation, and income on parental motivation and how this motivation subsequently influences the occurrence of temper tantrums in children with special needs. This research employed a quantitative path analysis design with a cross-sectional approach. The study was conducted at a Special Needs Primary School (SDLB) in Situbondo Regency, involving a total of 47 respondents selected through a total sampling technique. Data were collected via validated questionnaires and analyzed using multivariate linear regression to determine the mediating role of parental motivation. The findings reveal that socioeconomic factors significantly influence parental motivation, with path coefficients of 0.896 for education level, 2.062 for occupation, and 2.396 for income. Furthermore, parental motivation was found to have a direct and significant role in addressing temper tantrum issues, with a path coefficient of 0.68. Statistical analysis indicates that education, occupation, and income do not have a significant direct impact on temper tantrums in the absence of parental motivation. Parental motivation acts as a vital mediator between socioeconomic factors and the management of temper tantrums in children with special needs. The study underscores that while socioeconomic status provides a foundation, it is the parent’s internal motivation to accept and nurture their child that ultimately determines behavioral outcomes.